BRIDGING TRADITION AND INNOVATION: THE ROLE OF PINGXIANG NUO MASKS IN ANIMATION CHARACTER DESIGN - Zhu , Nian You; Subri , Shafilla Binti; Ramlie , Mohd Khairulnizam Bin; Zhou , Huan; Li , Pei Yao (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
The lack of integration and cultural representation in Pingxiang Nuo masks can reduce the aesthetic appeal of the audience, which is a challenge for the industry. The dysconnectivity of the audience with no emotions toward Pingxiang Nuo mask characters is problematic for the industry on a large scale. The purpose of this research is to measure the impact of Pingxiang Nuo mask funny role and positive supporting role on cultural expressiveness with mediating impact of artist qualification. The study is designed to provide comprehensive insight into contributing more value to the culture’s expressiveness. This study used a purposive sampling method to collect the data. This method was significant for sampling as students, teachers, professionals and audience of art design was population. A sample of 325 individuals, including students, teachers, professionals, and art design audiences, was collected. Smart PLS 4 was used for conducting statistical analysis with partial least square–structural equation modeling (PLS-SEM). The findings of this research contribute to the literature that the impact of Pingxiang Nuo masks funny role and a positive supporting role on cultural expressiveness is accepted. The study also confirmed that the effect of the Pingxiang Nuo influences the mediating role of artist qualification mask funny role and the positive supporting role of cultural expressiveness. The study asserts that the qualification of the artist is essential and significantly contributes to cultural expressiveness with the help of Pingxiang Nuo masks. In China, it is required to improve the cultural expressiveness with the help of Pingxiang Nuo mask that is required for cultural and historical representations. JEL Classification Codes: C10, C81, C87, C12.